No Comebacks - Forsyth, Frederick (Random House Group, 1972)
Deception, blackmail, murder, revenge - these are the themes of stories that move from London to the coast of Spain, from Mauritius to Dublin to Dordogne. Whether his subject is assassination by stealth, the cruel confidence trick or the cold shock of coincidence, Frederick Forsyth is never less than compulsive, the detail always authentic.
Keywords: Fiction